Silicon-carbon composite material, preparation method thereof and lithium ion battery
By using silicon-carbon composites with porous carbon particles combined with graphene in lithium-ion batteries, nano Si and nano M grow in situ in the graphene porous carbon pores, the volume expansion and circulation of silicon-based composites in lithium-ion batteries is solved. The problem of poor performance achieves high energy density and stable battery performance.
Patent Information
- Application Number
- CN202411413017.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
AI Technical Summary
The existing silicon-based composite materials expand large volumes, poor circulation performance and low conductivity when charged and discharged in lithium-ion batteries, resulting in difficult application, and the existing preparation process is complex and low efficiency.
Porous carbon particles are combined with graphene, nano Si and nano M grow in situ in the graphene porous carbon pores, the volume expansion of nano Si-M particles is supported by space, active metal M improves conductivity, amorphous carbon coating enhances structural stability In order to reduce the contact surface of Si-M and electrolyte, the stability of the SEI film is improved.
It significantly reduces the volume expansion of the material during the charging and discharging process, improves the conductivity and cycling stability, enhances the rate performance and charge and discharge efficiency, and realizes a high energy density lithium-ion battery negative electrode material.
Smart Images

Figure CN119297238A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a silicon-carbon composite material, a preparation method thereof and a lithium-ion battery. Background Art
[0002] Since its first appearance in the 1990s, lithium-ion batteries have gradually occupied the portable consumer electronics market represented by mobile phones and computers, and also have broad application prospects in large-scale energy storage and electric vehicles. The negative electrode materials of lithium-ion batteries have gradually evolved from coke to natural graphite, artificial graphite, etc. The technology of carbon-based negative electrodes has been very mature. However, the theoretical specific capacity of 372mAh / g can no longer meet people's growing requirements for energy density. The development of new negative electrode materials has become a top priority.
[0003] It has basically become an industry consensus that higher capacity silicon-based negative electrode materials are expected to be used in the next generation of high-energy density lithium-ion batteries. However, silicon-based composite materials have large volume expansion during charging and discharging, and low cycle performance and conductivity, making them difficult to use in power batteries.
[0004] At present, most of the research in this area is based on the simple combination of nano-silicon and carbon materials. No effective composite structure is formed, the expansion of the material during the charge and discharge process is not effectively suppressed, the rate performance and conductivity are poor, and the first efficiency and cycle retention rate are low. For example, Chinese patent with publication number CN109755522A discloses the use of commercially available nano-silicon, soft carbon, and carbon nanotubes for simple granulation and secondary carbon coating, but the preparation process is complicated, the nano-silicon particle size is large, the carbon material is simply composited, the structure is not dense, and the capacity and initial efficiency are low; Chinese patent with publication number CN115020689A discloses that metal oxides need to be deposited in porous carbon by hydrothermal chemical method technology, and then nano-silicon is deposited in porous carbon by CVD method, and then sintered and carbonized, but the composite effect is poor, the material conductivity, capacity and initial efficiency are low, and the rate performance is poor; Chinese patent with application number CN2021116039181 discloses that high-purity flake graphite is first prepared into expandable graphite; then the expandable graphite is prepared into expandable graphite in the reaction system, and silane is in an inert Under the protection of gas, silane is thermally decomposed to generate nano-silicon, which is deposited in and on the surface of expanded graphite sheets. Acetylene gas is introduced, and the reaction product enters the carbon coating section with the gas flow to form a composite negative electrode material with expanded graphite as the skeleton, nano-silicon deposited on the expanded graphite sheets and the surface, and then coated with a layer of carbon material on the outside. However, the preparation process is complicated and impurities in the expanded graphite are difficult to remove. It is necessary to first prepare the expanded graphite with flake graphite, and then deposit nano-Si on the surface and inside of the expanded graphite in a high-temperature furnace by silane, which has uneven deposition, poor composite effect, and low capacity and initial efficiency. The Chinese patent with publication number CN116130637A discloses that a gas phase silicon source and a pyrolytic carbon source are used to realize the in-situ composite of pyrolytic carbon with a nanometer thickness and pyrolytic nano-silicon by co-deposition from bottom to top, but the silane is deposited in the pyrolytic carbon, and the pole piece expands greatly. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a silicon-carbon composite material, a preparation method thereof and a lithium-ion battery.
[0006] The present invention provides a silicon-carbon composite material, comprising porous carbon particles, graphene, nano-Si and nano-M; the porous carbon particles are coated with graphene; nano-Si and nano-M are deposited inside the porous carbon particles, between the porous carbon particles and the graphene, and on the surface of the graphene;
[0007] The surfaces of the nano-Si and nano-M are coated with a carbon layer;
[0008] The surfaces of the porous carbon particles and graphene are coated with a carbon layer;
[0009] The M is selected from active metals.
[0010] Preferably, the M is selected from one or more of Al, Ti and Ni;
[0011] And / or, the mass ratio of the total mass of the nano-Si and the nano-M, the mass ratio of the porous carbon particles and the graphene is 40-55:55-60:1-10;
[0012] And / or, the specific surface area of the silicon-carbon composite material is 1 to 4 m 2 / g;
[0013] And / or, the pore size of the silicon-carbon composite material is 10 nm to 2 μm;
[0014] And / or, the particle size D50 of the silicon-carbon composite material is 7-10 μm.
[0015] The present invention also provides a method for preparing a silicon-carbon composite material, comprising the following steps:
[0016] S1) Preparation of C@G precursor:
[0017] The dispersant, the carbon source, the porous carbon particles and the graphene slurry are mixed and spray-dried to obtain a C@G precursor;
[0018] S2) Preparation of Nano-Si-M@CG Intermediate:
[0019] (1) heating the C@G precursor for preliminary carbonization;
[0020] (2) continuously introducing silicon source gas, metal M compound gas and inert protective gas to perform the first heat preservation treatment;
[0021] (3) stopping the introduction of silicon source gas and metal M compound gas, and continuously introducing carbon-containing gas and inert protective gas, and performing a second heat preservation treatment to obtain a nano-Si-M@CG intermediate; wherein M is selected from an active metal;
[0022] S3) Preparation of silicon-carbon composite material:
[0023] The nano-Si-M@CG intermediate is carbon coated to obtain a silicon-carbon composite material.
[0024] Preferably, the heating rate in step (1) is 5 to 20°C / min;
[0025] and / or, the temperature of the initial carbonization is 300° C. to 700° C.;
[0026] and / or, the initial carbonization time is 1 to 2 hours;
[0027] And / or, the preliminary carbonization is carried out under the condition of rotation; the rotation speed is 1-3r / min.
[0028] Preferably, the preliminary carbonization in step (1) is carried out under vacuum conditions, and after the preliminary carbonization, silicon source gas is introduced for direct heat preservation treatment.
[0029] Preferably, the vacuum degree of the vacuum condition is 1 to 100 Pa;
[0030] And / or, the ratio of the amount of silicon source gas introduced to the porous carbon particles is (50-150) L: 1 kg;
[0031] And / or, the temperature of the direct heat preservation treatment is 400° C. to 600° C.;
[0032] And / or, the direct heat preservation treatment time is 0.5 to 2 hours.
[0033] Preferably, in step (2), the flow rates of the silicon source gas, the metal M compound gas and the inert protective gas continuously introduced are independently 0.1 to 4 L / min;
[0034] And / or, the temperature of the first heat preservation treatment is 400° C. to 600° C.;
[0035] And / or, the first heat preservation treatment time is 5 to 10 hours;
[0036] And / or, the flow rates of the carbon-containing gas and the inert protective gas continuously introduced in step (3) are independently 1 to 5 L / min;
[0037] And / or, the temperature of the second heat preservation treatment is 600° C. to 700° C.;
[0038] And / or, the second heat preservation treatment time is 0.5 to 3 hours.
[0039] Preferably, the dispersant is selected from one or more of carboxymethyl cellulose, polyvinyl pyrrolidone, polyethylene glycol and sodium dodecyl carbonate;
[0040] The carbon source is selected from one or more of glucose, sucrose and polyacrylic acid;
[0041] The silicon source gas is selected from one or more of monosilane, trisilane, dichlorosilane, trichlorosilane and tetrachlorosilane;
[0042] The metal M-containing compound is selected from one or more of trimethylaluminum, aluminum hydride, nickel tetracarbonyl, 4-dimethylaminotitanium and titanium tetrachloride;
[0043] The carbon-containing gas is selected from one or more of acetylene, ethylene and propane.
[0044] Preferably, the carbon coating methods in step S3) are independently selected from pyrolysis and / or chemical vapor deposition.
[0045] The present invention also provides a lithium-ion battery comprising the above-mentioned silicon-carbon composite material.
[0046] The present invention provides a silicon-carbon composite material, comprising porous carbon particles, graphene, nano-Si and nano-M; the porous carbon particles are coated with graphene; nano-Si and nano-M are deposited inside the porous carbon particles, between the porous carbon particles and the graphene, and on the surface of the graphene; the surfaces of the nano-Si and nano-M are coated with a carbon layer; the surfaces of the porous carbon particles and the graphene are coated with a carbon layer; the M is selected from active metals. Compared with the prior art, the silicon-carbon composite material provided by the present invention has nano-Si and nano-M in-situ grown in a porous carbon channel structure wrapped with graphene. The three-dimensional structure of the porous carbon wrapped with graphene can provide space for the volume expansion of nano-Si-M particles. The M particles effectively improve the electrical conductivity of the nano-Si-M. At the same time, the coating of amorphous carbon improves the structural stability of the composite material, reduces the specific surface area of the porous carbon material, and reduces the volume expansion of the material during the charge and discharge process. The coating of graphene reduces the contact area between the nano-Si-M and the electrolyte, improves the stability of the SEI film of the composite material, improves the cycle efficiency and cycle stability of the composite material, and the improvement of the electrical conductivity of the powder is helpful to exert the rate performance of the composite material.
[0047] Experimental results show that the silicon-carbon composite material provided by the present invention is assembled into a 2032 button-type battery, the first discharge capacity of which is 1900-2150 mAh / g, the first charge capacity is 1699-1935 mAh / g, and the charge and discharge efficiency is 89%-91%. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 Schematic diagram of the structure of the C@G precursor obtained in Example 1 of the present invention;
[0049] Figure 2 Schematic diagram of the structure of the silicon-carbon composite material obtained in Example 1 of the present invention;
[0050] Figure 3 This is a scanning electron microscope image of the nano-Si-Al@CG composite negative electrode material obtained in Example 1 of the present invention;
[0051] Figure 4 This is a scanning electron microscope image of the nano-Si@C composite negative electrode material obtained in Comparative Example 1 of the present invention;
[0052] Figure 5 This is a SEM-EDS image of a particle cross section of the nano Si-Al@CG composite negative electrode material obtained in Example 1 of the present invention;
[0053] Figure 6 This is the XRD diagram of the nano-Si-Al@CG composite negative electrode material obtained in Example 1 of the present invention;
[0054] Figure 7 This is the XRD diagram of the nano-Si@C composite negative electrode material obtained in Comparative Example 1 of the present invention;
[0055] Figure 8 This is the XRD diagram of the nano-Si@CG composite negative electrode material obtained in Comparative Example 2 of the present invention;
[0056] Fig. 9 is the XRD pattern of the nano-Si-Ti@CG composite material obtained in Example 2 of the present invention;
[0057] Fig.10 The first charge and discharge curves of the nano-Si@C, nano-Si@CG, and nano-Si-Al@CG composite negative electrode material electrode sheets prepared in Comparative Example 1, Comparative Example 2, and Example 1 of the present invention;
[0058] Fig.11 This is a cycle performance diagram of the nano-Si@C, nano-Si@CG, and nano-Si-Al@CG composite negative electrode material electrode sheets prepared in Comparative Example 1, Comparative Example 2, and Example 1 of the present invention. DETAILED DESCRIPTION
[0059] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0060] The present invention provides a silicon-carbon composite material, comprising porous carbon particles, graphene, nano-Si and nano-M; the porous carbon particles are coated with graphene; nano-Si and nano-M are deposited inside the porous carbon particles, between the porous carbon particles and the graphene, and on the surface of the graphene; the surfaces of the nano-Si and nano-M are coated with a carbon layer; the surfaces of the porous carbon particles and the graphene are coated with a carbon layer; and M is an active metal.
[0061] According to the present invention, the porous carbon particles are located in a cage-like structure formed by graphene; the porous carbon particles and graphene are preferably connected by amorphous carbon; the porous carbon-amorphous carbon-graphene composite structure is stable and can more effectively inhibit silicon carbon expansion. The porous carbon particles have a pore structure, and nano-Si and nano-M are loaded inside and on the surface; the particle sizes of the nano-Si and nano-M are independently preferably 0.5 to 10 nm, and more preferably 1 to 10 nm. The nano-Si-M particles have high electrical conductivity, which effectively improves the rate performance of nano-Si.
[0062] According to the present invention, the porous carbon particles and the graphene as well as the surface of the graphene are also loaded with nano-Si and nano-M.
[0063] According to the present invention, M is an active metal; the active metal may be any active metal well known to those skilled in the art without any special limitation, and in the present invention, it is preferably one or more of Al, Ti and Ni.
[0064] According to the present invention, the surface of the nano-Si and nano-M is coated with a carbon layer; the surface of the porous carbon particles and graphene is coated with a carbon layer; the carbon layer is preferably an amorphous carbon layer; the thickness of the carbon layer is preferably 2 to 20 nm. Amorphous carbon coating can improve the conductivity of the composite material, thereby increasing the battery rate performance.
[0065] According to the present invention, the mass ratio of the total mass of the nano-Si and the nano-M, and the mass ratio of the porous carbon particles to the graphene is preferably 40-55:55-60:1-10.
[0066] According to the present invention, the silicon-carbon composite material is preferably irregularly spherical and has a smooth surface.
[0067] According to the present invention, the surface of the silicon-carbon composite material has micropores; the pore diameter of the micropores is preferably 10 nm to 2 μm, more preferably 10 nm to 1 μm.
[0068] According to the present invention, the specific surface area of the silicon-carbon composite material is preferably 1 to 4 m 2 / g.
[0069] According to the present invention, the particle size D50 of the silicon-carbon composite material is preferably 7 to 12 μm, more preferably 7 to 10 μm.
[0070] The silicon-carbon composite material provided by the present invention has nano-Si and nano-M in-situ grown in a porous carbon channel structure wrapped with graphene. The three-dimensional structure of the porous carbon wrapped with graphene can provide space for the volume expansion of nano-Si-M particles. The M particles effectively improve the electrical conductivity of the nano-Si-M. At the same time, the coating of amorphous carbon improves the structural stability of the composite material, reduces the specific surface area of the porous carbon material, and reduces the volume expansion of the material during the charge and discharge process. The coating of graphene reduces the contact area between the nano-Si-M and the electrolyte, improves the stability of the SEI film of the composite material, improves the cycle efficiency and cycle stability of the composite material, and the improvement of the electrical conductivity of the powder is conducive to the performance of the rate performance of the composite material.
[0071] The present invention also provides a method for preparing a silicon-carbon composite material, comprising the following steps: S1) Preparation of a C@G precursor: mixing a dispersant, a carbon source, porous carbon particles and a graphene slurry, and spray drying to obtain a C@G precursor; S2) Preparation of a nano-Si-M@CG intermediate: (1) heating the C@G precursor for preliminary carbonization; (2) continuously introducing a silicon source gas, a metal M compound gas and an inert protective gas to perform a first heat preservation treatment; (3) stopping the introduction of the silicon source gas and the metal M compound gas, continuously introducing a carbon-containing gas and an inert protective gas to perform a second heat preservation treatment to obtain a nano-Si-M@CG intermediate; the M is selected from an active metal; S3) Preparation of a silicon-carbon composite material: carbon coating the nano-Si-M@CG intermediate to obtain a silicon-carbon composite material.
[0072] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.
[0073] First, a C@G precursor is prepared, and a dispersant, a carbon source, porous carbon particles and a graphene slurry are mixed and spray-dried to obtain a C@G precursor; the dispersant can be a dispersant well known to those skilled in the art, and there is no special limitation. In the present invention, it is preferably one or more of carboxymethyl cellulose, polyvinyl pyrrolidone, polyethylene glycol and sodium dodecyl carbonate; the molecular weight of the carboxymethyl cellulose is preferably 80000-90000 g / mol; the degree of substitution of the carboxymethyl cellulose is preferably 0.78-0.88, more preferably 0.78-0.85, and more preferably 0.78-0.82, The most preferred value is 0.80; the molecular weight of the polyethylene glycol is preferably 10000-20000 g / mol, more preferably 15000-20000 g / mol, and more preferably 18000-20000 g / mol; the carbon source is any carbon source known to those skilled in the art, and there is no special limitation. In the present invention, it is preferably one or more of glucose, sucrose and polyacrylic acid; the molecular weight of the polyacrylic acid is preferably 5000-10000 g / mol, more preferably 8000-10000 g / mol; the pore volume of the porous carbon particles is preferably 0.7-1 m 3 / g; the particle size of the porous carbon particles is preferably 3 to 9 μm; the pore size of the porous carbon particles is preferably 1 to 20 nm; the specific surface area of the porous carbon particles is preferably 1400 to 2000 m 2 / g, more preferably 1500 to 2000 m 2 / g, preferably 1800-2000m 2 / g; In some embodiments provided by the present invention, the specific surface area of the porous carbon particles is specifically 1900m 2 / g; the porous carbon particles are preferably one or more of bio-based porous carbon particles, resin-based porous carbon particles and coal tar-based porous carbon particles; the concentration of the graphene slurry is preferably 1% to 5%, more preferably 2% to 4%, more preferably 2% to 3%, and most preferably 2.5% to 3%; the sheet diameter (diameter) D50 of the graphene in the graphene slurry is preferably 200nm to 20μm, more preferably 1 to 20μm, more preferably 1 to 15μm, more preferably 1 to 10μm, and most preferably 2 to 7μm; the number of graphene layers is preferably 1 to 30 layers, more preferably 5 to 25 layers, and more preferably 7 to 20 layers; the graphene slurry can be prepared by intercalation exfoliation, oxidation exfoliation, mechanical exfoliation, etc.; the mass ratio of the dispersant, carbon source, porous carbon particles and graphene slurry is (0.01 to 0.05): (0.005 to 0.03) :1:(1~5), more preferably (0.01~0.03):(0.01~0.03):1:(1~3), and more preferably (0.01~0.02):(0.01~0.03):1:(1~2); In some embodiments provided by the present invention, the mass ratio of the dispersant, the carbon source, the porous carbon particles and the graphene slurry is specifically 0.01:0.01:1:2, 0.02:0.01:1 :2, 0.01:0.01:1:1 or 0.01:0.03:1:1; the inlet air temperature of the spray drying is preferably 200℃~250℃, more preferably 210℃~240℃, and more preferably 220℃~230℃; the outlet air temperature of the spray drying is preferably 80℃~100℃, more preferably 85℃~95℃, and more preferably 90℃; the feed amount of the spray drying is preferably 0.2~0.9m 3 / h, more preferably 0.4 to 0.8 m 3 / h, preferably 0.5m 3 / h; the linear speed of the spray drying is preferably 18-30 m / s, more preferably 20-30 m / s, further preferably 25-30 m / s, and most preferably 28 m / s.
[0074] The C@G precursor is heated for preliminary carbonization; the heating rate of the heating is preferably 5-20°C / min, more preferably 5-15°C / min, more preferably 5-10°C / min, and most preferably 5°C / min; the temperature of the preliminary carbonization, that is, the insulation temperature, is preferably 300°C-700°C, more preferably 400°C-700°C, and more preferably 500°C-600°C; in some embodiments provided by the present invention, the temperature of the preliminary carbonization is specifically 500°C, 550°C or 600°C; the time of the preliminary carbonization, that is, the insulation time, is preferably 1-2h, more preferably 1-1.5h, and more preferably 1h; in order to make the C@G precursor heated evenly, the preliminary carbonization is preferably carried out under rotating conditions; the rotation speed is preferably 1-3 rpm, more preferably 1-2 rpm.
[0075] In another specific embodiment provided by the present invention, the preliminary carbonization is preferably carried out under vacuum conditions, and after the preliminary carbonization, silicon source gas is introduced for direct heat preservation treatment; the vacuum degree of the vacuum condition is preferably 1-100Pa, more preferably 1-80Pa, more preferably 5-50Pa, more preferably 5-30Pa, more preferably 5-20Pa, more preferably 8-15Pa, and most preferably 10Pa; the type of the silicon source gas is a silicon source gas well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably one or more of monosilane, trisilane, dichlorosilane, trichlorosilane and tetrachlorosilane; the ratio of the amount of silicon source gas introduced to the porous carbon particles is preferably (50-150) L: 1kg, more preferably (80-120)L: 1kg, and more preferably 100L: 1kg; the temperature of the direct heat preservation treatment is preferably 400℃-600℃, more preferably 450℃-600℃, more preferably 500℃-600℃, and most preferably 520℃-600℃; in some embodiments provided by the present invention, the temperature of the direct heat preservation treatment is specifically 520℃ or 600℃; if the temperature of the direct heat preservation treatment is higher than the temperature of the preliminary carbonization, the heating rate is preferably 5-20℃ / min, more preferably 5-15℃ / min, and more preferably 5-10℃ / min; the time of the direct heat treatment is preferably 0.5-2h, more preferably 0.8-1.5h, and more preferably 1h. The purpose of introducing the silicon source gas under vacuum is to first deposit nano-Si as an active point to improve the efficiency of subsequent continuous introduction.
[0076] After the initial carbonization or the end of direct heat preservation, silicon source gas, metal M compound gas and inert protective gas are continuously introduced to carry out the first heat preservation treatment; the silicon source gas is the same as described above and will not be repeated here. It can be the same as or different from the silicon source gas introduced during the direct heat preservation treatment, and there is no special limitation; the metal M compound gas is preferably one or more of trimethylaluminum, aluminum hydride, nickel tetracarbonyl, 4-dimethylaminotitanium and titanium tetrachloride; the inert protective gas can be an inert protective gas well known to those skilled in the art, and there is no special limitation. In the present invention, nitrogen and / or argon are preferred; The flow rates of the silicon source gas, the metal M compound gas and the inert protective gas are each independently preferably 0.1 to 4 L / min; specifically, the flow rate of the silicon source gas is preferably 0.3 to 4 L / min, more preferably 0.5 to 4 L / min, more preferably 1 to 4 L / min, more preferably 2 to 4 L / min, and most preferably 2 to 3 L / min; specifically, the flow rate of the metal M compound gas is preferably 0.1 to 4 L / min, more preferably 0.1 to 3 L / min, more preferably 0.1 to 2 L / min, and most preferably 0.1 to 1 L / min, most preferably 0.1-0.5 L / min; in some embodiments provided by the present invention, the flow rate of the continuous introduction of the metal M compound gas is specifically 0.3 L / min, 0.1 L / min or 0.5 L / min; specifically, the flow rate of the continuous introduction of the inert protective gas is preferably 0.3-4 L / min, more preferably 0.5-4 L / min, more preferably 1-4 L / min, and most preferably 2-4 L / min; the temperature of the first insulation treatment is preferably 400°C-600°C, more preferably 450°C-600°C, and more preferably 500°C. ℃~600℃, most preferably 520℃~600℃; in some embodiments provided by the present invention, the temperature of the first insulation treatment is specifically 520℃ or 600℃; if the temperature of the first insulation treatment is higher than the temperature of the preliminary carbonization or direct insulation treatment, the heating rate is preferably 5~20℃ / min, more preferably 5~15℃ / min, and more preferably 5~10℃ / min; the time of the first insulation treatment is preferably 5~10h, more preferably 5~9h; in some embodiments provided by the present invention, the time of the first insulation treatment is specifically 5h, 6h or 9h. The present invention can better regulate the negative electrode material with better conductivity and better cyclability by adopting the ratio of nano-Si-M and porous carbon that can be controlled in situ by chemical vapor phase.
[0077] After the first insulation treatment is completed, the introduction of silicon source gas and metal M compound gas is stopped, and carbon-containing gas and inert protective gas are continuously introduced to carry out a second insulation treatment; the carbon-containing gas is preferably one or more of acetylene, ethylene and propane; the flow rate of the continuous introduction of carbon-containing gas and inert protective gas is independently preferably 1 to 5 L / min; specifically, the flow rate of the continuous introduction of carbon-containing gas is preferably 1 to 3 L / min, more preferably 1 to 2 L / min; specifically, the flow rate of the continuous introduction of inert protective gas is preferably 1 to 3 L / min, more preferably 1 to 2 L / min; the second insulation treatment is carried out. The temperature of the secondary insulation treatment is preferably 600°C to 700°C, more preferably 620°C to 700°C; in some embodiments provided by the present invention, the temperature of the second insulation treatment is specifically 620°C, 680°C or 700°C; if the temperature of the second insulation treatment is higher than the temperature of the first insulation treatment, the heating rate is preferably 5 to 20°C / min, more preferably 5 to 15°C / min, and more preferably 5 to 10°C / min; the time of the second insulation treatment is preferably 0.5 to 3h, more preferably 1 to 3h, more preferably 1.5 to 2.5h, and most preferably 2h.
[0078] After the second heat preservation treatment, the temperature is preferably lowered, sieved, and iron is removed to obtain a nano-Si-M@CG intermediate.
[0079] The nano-Si-M@CG intermediate is carbon-coated; by carbon coating, the specific surface area of the carbon-silicon composite material can be controlled; the carbon coating method is preferably a pyrolysis method and / or a chemical vapor deposition method; the pyrolysis method is specifically: the nano-Si-M@CG intermediate is mixed with an organic carbon source, dried, and carbonized and sintered in a protective atmosphere; the organic carbon source can be an organic carbon source well known to those skilled in the art, and there is no special limitation. In the present invention, it is preferably asphalt and / or a polymer; the polymer is preferably a phenolic resin; in the present invention, further specifically, the pyrolysis method is: the nano-Si-M@CG intermediate is mixed with asphalt, and sprayed during the drying process. The polymer is prepared by carbonizing and sintering in a protective atmosphere; the mass ratio of the nano-Si-M@CG intermediate to the asphalt is preferably 1:(0.01-0.1), more preferably 1:(0.03-0.08), more preferably 1:(0.04-0.06), and most preferably 1:0.05; the mixing method is a method well known to those skilled in the art and is not particularly limited. In the present invention, stirring is preferred; the stirring speed is preferably 100-200 r / min, more preferably 100-150 r / min; the mixing time is preferably 1-3 h, more preferably 1.5-2.5 h, and most preferably 2 h; the mass concentration of the polymer ethanol solution is preferably 10% to 20%, more preferably 15%; the ratio of the nano-Si-M@CG intermediate to the polymer ethanol solution is preferably 1kg: (0.5 to 2) L, more preferably 1kg: (0.5 to 1.5) L, more preferably 1kg: (0.8 to 1.2) L, and most preferably 1kg: 1L; the spray rate of the polymer ethanol solution is preferably 50 to 150 mL / min, more preferably 80 to 120 mL / min, and more preferably 100 mL / min; the drying method includes but is not limited to stirring evaporation, centrifugal drying, two-flow drying, flash drying and the like; the drying temperature is preferably 100°C to 120°C; the protective atmosphere is preferably nitrogen and / or argon; the carbonization sintering temperature is preferably 100°C to 120°C. The temperature, i.e., the holding temperature, is preferably 300°C to 700°C, more preferably 400°C to 700°C, more preferably 500°C to 600°C, and most preferably 600°C; the heating rate of carbonization sintering is preferably 5 to 20°C / min, more preferably 5 to 15°C / min, and more preferably 5 to 10°C / min; the carbonization sintering time, i.e., the holding time, is preferably 1 to 3h, more preferably 1.5 to 2.5h, and more preferably 2h; the chemical vapor deposition method is specifically: continuously introducing carbon-containing gas and inert protective gas into the nano-Si-M@CG intermediate under heating conditions for carbon coating; the heating rate of heating is preferably 5 to 20°C / min, more preferably 5 to 15°C / min, and more preferably 5 to 10°C / min; the flow rate of continuously introducing carbon-containing gas is preferably 0.3-10L / min, more preferably 0.5-10L / min, more preferably 0.5-8L / min, more preferably 0.5-5L / min, more preferably 0.5-3L / min, most preferably 1-2L / min; the flow rate of the continuous inert protective gas is preferably 0.3-10L / min, more preferably 0.5-10L / min, more preferably 0.5-8L / min, more preferably 1-5L / min, more preferably 2-5L / min, most preferably 4L / min; the temperature of the carbon coating is preferably 300℃-700℃, more preferably 400℃-700℃, more preferably 500℃-600℃, most preferably 600℃; the time of the carbon coating is preferably 1-5h, more preferably 2-4h, and more preferably 3h. .
[0080] After the carbon coating is completed, the temperature is preferably lowered to room temperature, sieved, and iron removed to obtain a silicon-carbon composite material.
[0081] The present invention also provides a lithium-ion battery comprising the above-mentioned silicon-carbon composite material.
[0082] More specifically, the lithium-ion battery includes a positive electrode, a negative electrode, a separator and an electrolyte; the material of the negative electrode includes the above-mentioned silicon-carbon composite material.
[0083] The three-dimensional structure of the silicon-carbon composite material provided by the present invention can provide space for the volume expansion of nano Si particles during the charge and discharge process, and the volume expansion is small; the composite of nano metals effectively improves the conductivity of Si particles, is beneficial to the transmission of electrons, and has excellent rate performance; the surface amorphous carbon coating layer can reduce the contact surface between the negative electrode material and the electrolyte, which is beneficial to the rapid exchange of lithium ions at the contact surface and improves the cycle efficiency; the composite coating of graphene and amorphous carbon improves the electronic conductivity of the material and has good cycle stability.
[0084] In order to further illustrate the present invention, a silicon-carbon composite material, a preparation method thereof and a lithium-ion battery provided by the present invention are described in detail below in conjunction with embodiments.
[0085] The reagents used in the following examples are all commercially available; the molecular weight of PVP used in the examples and comparative examples is 37900 g / mol; the porous carbon type is one of bio-based, resin-based, and coal-tar-based; the specific surface area of the porous carbon used in the examples is 1900 m 2 / g; asphalt is low-temperature asphalt; phenolic resin is liquid phenolic resin; the molecular weight of CMC is 80000g / mol, and the degree of substitution is 0.80; the molecular weight of polyethylene glycol is 20000g / mol, and the molecular weight of polyacrylic acid is 10000g / mol; the solid content of the graphene slurry used in the embodiments and comparative examples is 2.5%, the number of graphene flakes is 7 to 20 layers, and the diameter D50 of the graphene flakes is 2 to 7μm, which is purchased from Ningbo Zhaoxi Technology Co., Ltd.
[0086] Example 1
[0087] This embodiment provides a method for preparing a nano-Si-M@CG composite negative electrode material for a secondary lithium-ion battery, comprising:
[0088] (1) C@G precursor preparation process:
[0089] 10g PVP, 10g glucose, 1kg specific surface area of 1900m 2 / g porous carbon, 2kg graphene flakes with 7 to 20 layers, a graphene flake diameter D50 of 2 to 7 μm, and a solid content of 2.5% graphene slurry. The graphene slurry in all embodiments was purchased from Ningbo Zhaoxi Technology Co., Ltd., and then spray-dried after being mixed evenly. The feed amount of the spray-dried product was 0.5m 3 / h; the linear speed of spray drying is 28m / S, granulation is carried out, the drying air inlet temperature is 220℃, and the air outlet temperature is 90℃ to obtain C@G precursor.
[0090] (2) Preparation process of nano-Si-M@CG intermediate:
[0091] 1 kg of C@G precursor was placed in a vacuum furnace and the vacuum furnace was evacuated to 10 Pa. The vacuum furnace was rotated at 1 rpm, and the temperature was raised to 500°C at a rate of 5°C per minute for preliminary carbonization, and the temperature was kept for 1 hour, and the vacuuming was stopped; the temperature was raised to 520°C at a rate of 5°C per minute, 100L of monosilane was introduced, and the temperature was kept for 1 hour; then, while maintaining the temperature, monosilane was continuously introduced at a flow rate of 2L / min, and trimethylaluminum organic gas and nitrogen protective gas were continuously introduced at the same time, the flow rate of trimethylaluminum organic gas was 0.3L / min, and the flow rate of nitrogen protective gas was 2L / min, and the gas was continuously introduced for 6 hours; the heating was continued to be raised to 620°C at a rate of 5°C per minute, acetylene gas was continuously introduced at a flow rate of 1L / min and nitrogen was introduced at a flow rate of 2L / min, and the temperature was kept for 2 hours. The nano-Si-Al@CG intermediate was obtained by cooling, sieving with 400 mesh, and removing iron. The specific surface area of the nano-Si-Al@CG intermediate was measured by a specific surface area tester and was 27 m 2 / g.
[0092] (3) Preparation process of nano-Si-Al@CG:
[0093] 1kg of nano-Si-Al@CG material and 50g of asphalt powder were mixed in a stirring and fusion machine, stirred at a speed of 100r / min for 2h, and dried at 120℃. During the drying process, 1L of 15% phenolic resin ethanol solution (100mL / min, 10min) was sprayed into the material. After the material was dried, it was released from the stirring and fusion machine. The material was placed in an atmosphere rotary furnace, and under nitrogen protection, the temperature was raised to 600℃ for carbonization sintering at a rate of 5℃ per minute, kept warm for 2h, cooled to room temperature, sieved through 400 mesh, and iron was removed to obtain a nano-Si-Al@CG composite negative electrode material, which is a silicon-carbon composite material. The specific surface area of the nano-Si-Al@CG composite negative electrode material was measured by a specific surface area tester to be 2.1m 2 / g.
[0094] See also Figure 1 , Figure 1 Schematic diagram of the structure of the C@G precursor obtained in Example 1, wherein 1 is porous carbon and 2 is a graphene sheet.
[0095] See also Figure 2 , Figure 2 Schematic diagram of the structure of the silicon-carbon composite material obtained in Example 1, wherein 2 is a graphene sheet, 3 is nano-Si-M@ porous carbon, and 4 is nano-Si.
[0096] The nano-Si-Al@CG composite negative electrode material obtained in Example 1 was analyzed using a scanning electron microscope, and its scanning electron microscope image was obtained as follows: Figure 3 As shown. Figure 3 It can be seen that the nano-Si-M@CG composite material is an irregular spherical shape, with graphene and amorphous carbon wrapped inside and on the surface of the particles. The particle surface is smooth and has micropores. The size of the micropores ranges from 10nm to 1μm. Nano-Si-M particles are evenly filled on the surface and inside of the particles, and the particle size D50 ranges from 7μm to 12μm.
[0097] Figure 5 This is a SEM-EDS image of the particle cross section of the nano-Si-Al@CG composite material prepared in Example 1. In the image, it can be seen that the nano-Si-M particles are uniformly dispersed inside the porous carbon, and the nano-particle size is 1nm to 10nm.
[0098] The nano-Si-Al@CG composite material obtained in Example 1 was analyzed by X-ray diffraction, and its XRD pattern was obtained as follows: Figure 6 shown. Figure 6 The 2θ value at 26.59° is the peak of graphene, the 2θ value at 28.4° and 47.3° are the characteristic peaks of Si, and the 2θ value at 38°, 44° and 65° are the characteristic peaks of Al.
[0099] Comparative Example 1
[0100] Comparative Example 1 provides a method for preparing a nano-Si@C composite negative electrode material for a secondary lithium-ion battery.
[0101] The specific surface area of 1 kg is 1900 m 2 / g porous carbon was placed in a vacuum furnace and the vacuum furnace was evacuated to 10Pa. The vacuum furnace rotated 1 rpm, and the temperature was raised to 500℃ at a rate of 5℃ per minute for preliminary carbonization, and the temperature was kept for 1h, and the vacuum was stopped; the temperature was raised to 520℃ at a rate of 5℃ per minute, and 100L of monosilane was introduced, and the temperature was kept for 1h; then, on the basis of maintaining the temperature, monosilane gas was continuously introduced at a flow rate of 2L / min for 6 hours; the temperature was continued to be raised to 620℃ at a rate of 5℃ per minute, and acetylene gas was continuously introduced at a flow rate of 1L / min and nitrogen protective gas was introduced at a flow rate of 2L / min, and the temperature was kept for 2h. Cooling, 400 mesh sieving, and iron removal were performed to obtain the nano-Si@C intermediate. The specific surface area of the nano-Si@C intermediate was measured by a specific surface area tester to be 32m 2 / g.
[0102] 1kg of nano-Si@C intermediate material and 50g of asphalt powder were mixed in a stirring and fusion machine, stirred at a speed of 100r / min for 2h, and dried at 120℃. During the drying process, 1L of 15% phenolic resin ethanol solution (100mL / min, 10min) was sprayed into the material. After the material was dried, it was released from the stirring and fusion machine. The material was placed in an atmosphere furnace, and under nitrogen protection, the temperature was raised to 600℃ for carbonization sintering at a rate of 5℃ per minute, kept warm for 2h, cooled to room temperature, sieved through 400 mesh, and iron was removed to obtain a nano-Si@C composite negative electrode material. The specific surface area of the nano-Si@C composite negative electrode material was measured by a specific surface area tester to be 2.8m 2 / g.
[0103] The nano-Si@C composite negative electrode material obtained in Comparative Example 1 was analyzed using a scanning electron microscope, and the scanning electron microscope image thereof was obtained as follows: Figure 4 As shown. Figure 4 It can be seen that the nano-Si particles are distributed in the pores of the porous carbon, the particle size distribution is uniform, and the particle size range is 1nm to 10nm.
[0104] The nano-Si@C composite negative electrode material obtained in Comparative Example 1 was analyzed by X-ray diffraction, and its XRD pattern was obtained as follows: Figure 7 As shown. Figure 7 It can be seen that 2θ at 28.4° and 47.3° are characteristic peaks of Si, the peak of nano-Si is an elliptical peak, and the nano-Si inside the surface is amorphous.
[0105] Comparative Example 2
[0106] (1) C@G precursor preparation process:
[0107] 10g PVP, 10g glucose, 1kg specific surface area of 1900m 2 / g porous carbon and 2kg graphene slurry with a solid content of 2.5% were mixed evenly and then spray dried for granulation. The feed amount of the spray drying was 0.5m 3 / h; the linear speed of spray drying was 28m / S, the drying air inlet temperature was 220°C, and the air outlet temperature was 90°C to obtain a C@G precursor.
[0108] (2) Preparation process of nano-Si@CG intermediates:
[0109] 1kg of C@G precursor was placed in a vacuum furnace and the vacuum furnace was evacuated to 10Pa. The vacuum furnace rotated 1 rpm, and the temperature was raised to 500℃ at a rate of 5℃ per minute for preliminary carbonization. The temperature was kept for 1 hour, and the vacuum was stopped; the temperature was raised to 520℃ at a rate of 5℃ per minute, and 100L of monosilane was introduced, and the temperature was kept for 1 hour; then, on the basis of maintaining the temperature, monosilane gas was continuously introduced at a flow rate of 2L / min for 6 hours; the temperature was continued to be raised to 620℃ at a rate of 5℃ per minute, and acetylene gas was continuously introduced at a flow rate of 1L / min and nitrogen protective gas was introduced at a flow rate of 2L / min, and the temperature was kept for 2 hours. Cooling, 400 mesh screening, and iron removal were performed to obtain the nano-Si@CG intermediate. The specific surface area of the nano-Si@CG intermediate was measured by a specific surface area tester to be 25m 2 / g.
[0110] (3) Preparation process of nano-Si@CG composite negative electrode material:
[0111] 1kg of nano-Si@CG intermediate material and 50g of asphalt powder were mixed in a stirring and fusion machine, stirred at a speed of 100r / min for 2h, and dried at 120℃. During the drying process, 1L of 15% phenolic resin ethanol solution (100mL / min, 10min) was sprayed into the material. After the material was dried, it was released from the stirring and fusion machine. The material was placed in an atmosphere furnace, and under nitrogen protection, the temperature was raised to 600℃ for carbonization sintering at a rate of 5℃ per minute, kept warm for 2h, cooled, sieved with 400 mesh, and iron removed to obtain a nano-Si@CG composite negative electrode material. The specific surface area of the nano-Si@CG composite negative electrode material was measured by a specific surface area tester to be 3.1m 2 / g, as a comparative test material. The source of the raw material components of the silicon-containing gas is not particularly limited, and can be generally commercially available.
[0112] The nano-Si@CG composite negative electrode material obtained in Comparative Example 2 was analyzed by X-ray diffraction, and its XRD pattern was as follows: Figure 8 shown. Figure 8 The 2θ value at 26.59° is the peak of graphene, the 2θ value at 28.4° and 47.3° are the characteristic peaks of Si, the peak of nano-Si is an elliptical peak, and the nano-Si inside the surface is amorphous.
[0113] The nano-Si@C, nano-Si@CG, and nano-Si-Al@CG composite negative electrode materials prepared in Comparative Example 1, Comparative Example 2, and Example 1 were subjected to electrochemical performance tests. The 2032 button cell was prepared and the electrochemical performance was tested as follows: the mass ratio of the composite negative electrode material, carbon black, and CMC+SBR was 90:5:5, the composite negative electrode material and carbon black were mixed evenly, and then a 2% CMC+40% SBR aqueous solution was added, coated on a Cu foil with a thickness of 40 μm, and vacuum dried at 120°C in a vacuum drying oven for 24 hours, an electrode sheet with a diameter of 1.6 cm was taken as the working electrode, a metal lithium sheet was taken as the counter electrode, and the electrolyte was 1 mol / L LiPF6 / EC-DMC-EMC (volume ratio 1:1:1), and a 2032 button cell was assembled in a glove box filled with Ar gas. The charge and discharge voltage range is 1.5 to 0.005 V, the charge and discharge current of the first cycle is 200 mA / g (0.1C), and the charge and discharge current density after the first cycle is 400 mA / g (0.2C).
[0114] The nano-Si@C, nano-Si@CG, and nano-Si-Al@CG composite negative electrode materials prepared in Comparative Example 1, Comparative Example 2, and Example 1 were subjected to in-situ electrode sheet expansion tests. The ternary positive electrode sheet is the counter electrode, and the nickel cobalt manganese oxide ternary positive electrode material (LiNi 0.8 Co 0.1 Mn 0.1 O2), carbon black and PVDF in a mass ratio of 80:10:10, the ternary cathode material and carbon black are mixed evenly, and then solvent NMP is added, coated on Al foil with a thickness of 40 μm, and vacuum dried in a vacuum drying oven at 120°C for 24 hours, and a ternary material cathode electrode sheet with a diameter of 1.6 cm is taken as a counter electrode, and the negative electrode sheet (the preparation method of the negative electrode sheet is the same as the working electrode described above) and the ternary material cathode electrode sheet are assembled into a button battery full battery, and the battery electrolyte adopts ternary material electrolyte 1mol / L LiPF6 / EC-DMC-EMC (volume ratio 1:1:1), and the thickness change of the electrode sheet under charge and discharge expansion is tested in an in-situ button expansion instrument, the charge and discharge voltage range is 3-4.2V, and the charge and discharge rate of 1-3 cycles is 0.1C, and the results are as follows Fig.10 , Fig.11 As shown in Table 1.
[0115] After testing, the first discharge capacity of the nano-Si@C composite negative electrode material is 1870mAh / g, the first charging capacity is 1652mAh / g, the charge and discharge efficiency is 88%, and the retention rate of 500 cycles at 0.2C is 93%; the first discharge capacity of the nano-Si@CG composite negative electrode material is 1903mAh / g, the first charging capacity is 1695mAh / g, the charge and discharge efficiency is 89%, and the retention rate of 500 cycles at 0.2C is 94%; the first discharge capacity of the nano-Si-Al@CG composite negative electrode material is 1905mAh / g, the first charging capacity is 1717mAh / g, the charge and discharge efficiency is 90%, and the retention rate of 500 cycles at 0.2C is 97%. The in-situ electrode sheet expansion rates of 1, 2, and 3 cycles of nano-Si@C composite negative electrode material are 50.3%, 39.09%, and 36%, respectively; the in-situ electrode sheet expansion rates of 1, 2, and 3 cycles of nano-Si@CG composite negative electrode material are 45%, 41.79%, and 40%, respectively; the in-situ electrode sheet expansion rates of 1, 2, and 3 cycles of nano-Si-Al@CG composite negative electrode material are 26.38%, 9.57%, and 8.7%, respectively.
[0116] Fig.10 It is the first charge and discharge curve diagram of the nano-Si@C, nano-Si@CG, and nano-Si-Al@CG composite negative electrode material electrode sheets prepared in Comparative Example 1, Comparative Example 2, and Example 1.
[0117] Fig.11 This is a cycle performance diagram of the nano-Si@C, nano-Si@CG, and nano-Si-Al@CG composite negative electrode material electrode sheets prepared in Comparative Example 1, Comparative Example 2, and Example 1.
[0118] Table 1 Thickness change results of electrode sheet under charge and discharge expansion
[0119]
[0120] It can be seen from Table 1 that the first charge and discharge thickness of the electrode sheets of the nano-Si@C, nano-Si@CG, and nano-Si-Al@CG composite negative electrode materials prepared in Comparative Example 1, Comparative Example 2, and Example 1 of the present invention, and the first efficiency, cycle retention rate, and in-situ electrode sheet expansion index of the nano-Si-Al@CG composite negative electrode material are better.
[0121] Example 2
[0122] This embodiment provides a method for preparing a nano-Si-M@CG composite negative electrode material for a secondary lithium-ion battery, comprising:
[0123] (1) C@G precursor preparation process:
[0124] 20g PVP, 10g glucose, 1kg porous carbon, and 2kg 2.5% graphene slurry were mixed and spray dried. The feed amount of the spray drying was 0.5m 3 / h; the linear speed of spray drying is 28m / S, granulation is carried out, the drying air inlet temperature is 220℃, and the air outlet temperature is 90℃ to obtain C@G precursor.
[0125] (2) Preparation process of nano-Si-M@CG intermediate:
[0126] 1kg C@G precursor was placed in a vacuum furnace and the vacuum furnace was evacuated to 10Pa. The vacuum furnace rotated 1 rpm, and the temperature was raised to 500℃ at a rate of 5℃ per minute for preliminary carbonization, and the temperature was kept for 1h, and the vacuum was stopped; the temperature was raised to 520℃ at a rate of 5℃ per minute, and 100L monosilane was introduced, and the temperature was kept for 1h; then, on the basis of maintaining the temperature, monosilane was continuously introduced at a flow rate of 2L / min, and 4-dimethylaminotitanium gas and nitrogen protective gas were continuously introduced at the same time. The flow rate of 4-dimethylaminotitanium gas was 0.3L / min, and the flow rate of nitrogen protective gas was 2L / min, and the gas was continuously introduced for 6 hours; the temperature was continued to be raised to 620℃ at a rate of 5℃ per minute, and acetylene gas was continuously introduced at a flow rate of 1L / min and nitrogen was introduced at a flow rate of 2L / min, and the temperature was kept for 2h. The nano Si-Ti@CG intermediate was obtained by cooling, sieving with 400 mesh, and removing iron.
[0127] (3) Preparation process of nano-Si-Ti@CG:
[0128] 1kg of nano-Si-Ti@CG intermediate material and 50g of asphalt powder were mixed in a stirring and fusion machine, stirred at a speed of 150r / min for 2h, and dried at 120°C. During the drying process, 1L of 15% phenolic resin ethanol solution (100mL / min, 10min) was sprayed into the material, and the material was released from the stirring and fusion machine after drying. The material was placed in an atmosphere rotary furnace, heated to 600°C for carbonization and sintering at a rate of 5°C per minute under nitrogen protection, kept warm for 2h, cooled to room temperature, sieved with 400 mesh, and iron removed to obtain a nano-Si-Ti@CG composite negative electrode material.
[0129] According to the above method, a 2032 button half-cell test was prepared and tested under the condition of charge and discharge voltage range of 1.5~0.005V; according to the above method, a button cell full cell with a ternary positive electrode as the counter electrode was prepared and tested under the condition of charge and discharge voltage range of 3~4.2V. After testing, the first discharge capacity of the nano Si-Ti@CG composite negative electrode material was 1900mAh / g, the first charge capacity was 1706mAh / g, the charge and discharge efficiency was 89.8%, and the lithium removal capacity at 0.2C rate was 1645mAh / g.
[0130] The nano-Si-Ti@CG composite material obtained in Example 2 was analyzed by X-ray diffraction, and its XRD pattern was obtained as follows: Fig. 9 shown. Fig. 9 Among them, 2θ at 26.59° is the peak of graphene, 2θ at 28.4° and 47.3° are the characteristic peaks of Si, and 2θ at 40° is the characteristic peak of Ti.
[0131] Example 3
[0132] This embodiment provides a method for preparing a nano-Si-M@CG composite negative electrode material for a secondary lithium-ion battery, comprising:
[0133] (1) C@G precursor preparation process:
[0134] 10g PVP, 10g sucrose, 1kg porous carbon, and 2kg 2.5% graphene slurry were mixed and spray dried. The feed amount of the spray drying was 0.5m 3 / h; the linear speed of spray drying is 28m / S, granulation is carried out, the drying air inlet temperature is 220℃, and the air outlet temperature is 90℃ to obtain C@G precursor.
[0135] (2) Preparation process of nano-Si-M@CG intermediate:
[0136] 1kg C@G precursor was placed in a vacuum furnace and the vacuum furnace was evacuated to 10Pa. The vacuum furnace rotated 1 rpm, and the temperature was raised to 500℃ at a rate of 5℃ per minute for preliminary carbonization, and the temperature was kept for 1h, and the vacuum was stopped; the temperature was raised to 520℃ at a rate of 5℃ per minute, and 100L monosilane was introduced, and the temperature was kept for 1h; then monosilane was continuously introduced at a flow rate of 2L / min on the basis of maintaining the temperature, and tetracarbonyl nickel gas and nitrogen protective gas were continuously introduced at the same time, the flow rate of tetracarbonyl nickel gas was 0.3L / min, and the flow rate of nitrogen protective gas was 2L / min, and the gas was continuously introduced for 6 hours; the temperature was continued to be raised to 620℃ at a rate of 5℃ per minute, and acetylene gas was continuously introduced at a flow rate of 1L / min and nitrogen protective gas was introduced at a flow rate of 2L / min, and the temperature was kept for 2h. The nano-Si-Ni@CG intermediate was obtained by cooling, sieving with 400 mesh, and removing iron.
[0137] (3) Preparation process of nano-Si-Ni@CG:
[0138] 1kg of nano-Si-Ni@CG intermediate material and 50g of asphalt powder were mixed in a stirring and fusion machine, stirred at a speed of 150r / min for 2h, and dried at 120°C. During the drying process, 1L of 10% phenolic resin ethanol solution (100mL / min, 10min) was sprayed into the material, and the material was released from the stirring and fusion machine after drying. The material was placed in an atmosphere rotary furnace, and under nitrogen protection, the temperature was raised to 600°C for carbonization sintering at a rate of 5°C per minute, kept warm for 2h, cooled to room temperature, sieved with 400 mesh, and iron removed to obtain a nano-Si-Ni@CG composite negative electrode material.
[0139] According to the above method, a 2032 button half-cell test was prepared and tested under the condition of charge and discharge voltage range of 1.5~0.005V; according to the above method, a button cell full cell with a ternary positive electrode as the counter electrode was prepared and tested under the condition of charge and discharge voltage range of 3~4.2V. After testing, the first discharge capacity of the nano-Si-Ni@CG composite negative electrode material was 1909mAh / g, the first charge capacity was 1699mAh / g, the charge and discharge efficiency was 89%, and the lithium removal capacity at 0.2C rate was 1602mAh / g.
[0140] Example 4
[0141] This embodiment provides a method for preparing a nano-Si-M@CG composite negative electrode material for a secondary lithium-ion battery, comprising:
[0142] (1) C@G precursor preparation process:
[0143] 10g CMC, 10g glucose, 1kg porous carbon, and 1kg 2.5% graphene slurry were mixed and spray dried. The feed amount of the spray drying was 0.5m 3 / h; the linear speed of spray drying is 28m / S, granulation is carried out, the drying air inlet temperature is 220℃, and the air outlet temperature is 90℃ to obtain C@G precursor.
[0144] (2) Preparation process of nano-Si-Al@CG intermediate:
[0145] 1kg C@G precursor was placed in a vacuum furnace and the vacuum furnace was evacuated to 50Pa. The vacuum furnace rotated 1 rpm, and the temperature was raised to 600℃ at a rate of 5℃ per minute for preliminary carbonization. The temperature was kept for 1h, and the vacuum was stopped; the temperature was kept at 600℃, and 100L dichlorosilane was introduced for 2h; then dichlorosilane was continuously introduced at a flow rate of 3L / min on the basis of maintaining the temperature, and aluminum hydride organic gas and nitrogen protective gas were continuously introduced at the same time. The flow rate of aluminum hydride organic gas was 0.5L / min; the flow rate of nitrogen protective gas was 4L / min, and the gas was continuously introduced for 5 hours; the temperature was continued to be raised to 680℃ at a rate of 5℃ per minute, and acetylene and propane gas with a gas ratio of 1:1 was continuously introduced at 2L / min, and the inert protective gas flow rate was 2L / min, and the temperature was kept for 2h. The nano Si-Al@CG intermediate was obtained by cooling, sieving with 400 mesh, and removing iron.
[0146] (3) Preparation process of nano-Si-Al@CG:
[0147] 1 kg of nano-Si-Al@CG material was placed in an atmosphere rotary furnace. Under nitrogen protection, the temperature was raised to 600°C at a rate of 5°C per minute, and acetylene gas was continuously introduced at a rate of 2 L / min and nitrogen gas at a flow rate of 4 L / min. The material was kept warm for 3 hours, cooled to room temperature, sieved through 400 mesh, and iron was removed to obtain the nano-Si-Al@CG composite negative electrode material.
[0148] According to the above method, a 2032 button half-cell test was prepared and tested under the condition of charge and discharge voltage range of 1.5~0.005V; according to the above method, a button cell full cell with a ternary positive electrode as the counter electrode was prepared and tested under the condition of charge and discharge voltage range of 3~4.2V. After testing, the first discharge capacity of the nano Si-Al@CG composite negative electrode material was 2100mAh / g, the first charge capacity was 1890mAh / g, the charge and discharge efficiency was 90%, and the lithium removal capacity at 0.2C rate was 1842mAh / g.
[0149] Example 5
[0150] This embodiment provides a method for preparing a nano-Si-M@CG composite negative electrode material for a secondary lithium-ion battery, comprising:
[0151] (1) C@G precursor preparation process:
[0152] 10g polyethylene glycol, 30g polyacrylic acid, 1kg porous carbon, and 1kg 2.5% graphene slurry were mixed and spray dried. The feed amount of the spray drying was 0.5m 3 / h; the linear speed of spray drying is 28m / S, granulation is carried out, the drying air inlet temperature is 220℃, and the air outlet temperature is 90℃ to obtain C@G precursor.
[0153] (2) Preparation process of nano-Si-Al@CG intermediate:
[0154] 1kg C@G precursor was placed in an atmosphere rotary furnace, which rotated at 2 rpm, and heated to 550℃ at a rate of 5℃ per minute for preliminary carbonization, and kept warm for 1h; heated to 600℃ at a rate of 5℃ per minute, and trichlorosilane was continuously introduced at a flow rate of 3L / min, and aluminum hydride organic gas and nitrogen protective gas were continuously introduced at the same time, the flow rate of aluminum hydride organic gas was 0.5L / min, and the flow rate of nitrogen protective gas was 4L / min, and the gas was continuously introduced for 5 hours; continued to heat to 700℃ at a rate of 5℃ per minute, and ethylene gas was continuously introduced at a flow rate of 2L / min and nitrogen gas at a flow rate of 2L / min, and kept warm for 2h. Cooling, 400 mesh sieving, and iron removal were performed to obtain nano Si-Al@CG intermediate.
[0155] (3) Preparation process of nano-Si-Al@CG:
[0156] 1 kg of nano-Si-Al@CG material was placed in an atmosphere rotary furnace. Under nitrogen protection, the temperature was raised to 600°C at a rate of 5°C per minute. Acetylene gas was continuously introduced at a flow rate of 1.2 L / min and nitrogen gas at a flow rate of 4 L / min. The material was kept warm for 2 h, cooled to room temperature, sieved through 400 mesh, and iron was removed to obtain a nano-Si-Al@CG composite negative electrode material.
[0157] According to the above method, a 2032 button half-cell test was prepared and tested under the condition of charge and discharge voltage range of 1.5~0.005V; according to the above method, a button cell full cell with a ternary positive electrode as the counter electrode was prepared and tested under the condition of charge and discharge voltage range of 3~4.2V. After testing, the first discharge capacity of the nano Si-Al@CG composite negative electrode material was 2041mAh / g, the first charge capacity was 1837mAh / g, the charge and discharge efficiency was 90%, and the lithium removal capacity at 0.2C rate was 1787mAh / g.
[0158] Example 6
[0159] This embodiment provides a method for preparing a nano-Si-M@CG composite negative electrode material for a secondary lithium-ion battery, comprising:
[0160] (1) C@G precursor preparation process:
[0161] 10g polyethylene glycol, 10g glucose, 1kg porous carbon, and 1kg 3% graphene slurry were mixed and spray dried. The feed amount of the spray drying was 0.5m 3 / h; the linear speed of spray drying is 28m / S, granulation is carried out, the drying air inlet temperature is 220℃, and the air outlet temperature is 90℃ to obtain C@G precursor.
[0162] (2) Preparation process of nano-Si-Al@CG intermediate:
[0163] 1kg C@G precursor was placed in an atmosphere rotary furnace, which rotated at 2 rpm, and heated to 500℃ at a rate of 5℃ per minute for preliminary carbonization, and kept warm for 1h; heated to 600℃ at a rate of 5℃ per minute, and trichlorosilane was continuously introduced at a flow rate of 3L / min, and aluminum hydride organic gas and argon protective gas were continuously introduced at a flow rate of 0.1L / min and argon protective gas at a flow rate of 2L / min, and the gas was continuously introduced for 9 hours; continued heating was heated to 620℃ at a rate of 5℃ per minute, and acetylene gas and argon were continuously introduced at a flow rate of 1L / min and 2L / min, and kept warm for 2h. Cooling, 400 mesh sieving, and iron removal were performed to obtain nano-Si-Al@CG intermediate.
[0164] (3) Preparation process of nano-Si-Al@CG:
[0165] 1 kg of nano-Si-Al@CG intermediate material was placed in an atmosphere rotary furnace. Under nitrogen protection, the temperature was raised to 600°C at a rate of 5°C per minute, and acetylene gas and nitrogen were continuously introduced. The flow rate of acetylene gas was 1.2 L / min and the flow rate of nitrogen was 4 L / min. The material was kept warm for 3 hours, cooled to room temperature, sieved with 400 mesh, and iron was removed to obtain the nano-Si-Al@CG composite negative electrode material.
[0166] According to the above method, a 2032 button half-cell test was prepared and tested under the condition of charge and discharge voltage range of 1.5~0.005V; according to the above method, a button cell full cell with a ternary positive electrode as the counter electrode was prepared and tested under the condition of charge and discharge voltage range of 3~4.2V. After testing, the first discharge capacity of the nano Si-Al@CG composite negative electrode material was 2150mAh / g, the first charge capacity was 1935mAh / g, the charge and discharge efficiency was 91%, and the lithium removal capacity at 0.2C rate was 1876mAh / g.
[0167] Example 7
[0168] This embodiment provides a method for preparing a nano-Si-M@CG composite negative electrode material for a secondary lithium-ion battery, comprising:
[0169] (1) C@G precursor preparation process:
[0170] 10 g of polyethylene glycol, 10 g of sucrose, 1 kg of porous carbon and 2 kg of 3% graphene slurry were mixed and then spray dried. The feed amount of the spray drying was 0.5 m 3 / h; the linear speed of spray drying is 28m / S, granulation is carried out, the drying air inlet temperature is 220℃, and the air outlet temperature is 90℃ to obtain C@G precursor.
[0171] (2) Preparation process of nano-Si-Al@CG intermediate:
[0172] 1kg C@G precursor was placed in an atmosphere rotary furnace, which rotated 2 rpm, and heated to 500℃ at a rate of 10℃ per minute for preliminary carbonization, and kept warm for 1h; heated to 600℃ at a rate of 10℃ per minute, and trichlorosilane was continuously introduced at a flow rate of 2L / min, and aluminum hydride organic gas and argon were continuously introduced at a flow rate of 0.3L / min and argon at a flow rate of 2L / min, and the gas was continuously introduced for 6 hours; continued heating was heated to 620℃ at a rate of 10℃ per minute, and acetylene gas was continuously introduced at a flow rate of 1L / min and argon at a flow rate of 2L / min, and kept warm for 2h. Cooling, 400 mesh sieving, and iron removal were performed to obtain nano-Si-Al@CG intermediate.
[0173] (3) Preparation process of nano-Si-Al@CG:
[0174] 1 kg of nano-Si-Al@CG intermediate material was placed in an atmosphere rotary furnace. Under nitrogen protection, the temperature was raised to 600°C at a rate of 10°C per minute, and acetylene gas and nitrogen were continuously introduced. The flow rate of acetylene gas was 1.2 L / min and the flow rate of nitrogen was 4 L / min. The material was kept warm for 3 hours, cooled to room temperature, sieved with 400 mesh, and iron was removed to obtain the nano-Si-Al@CG composite negative electrode material.
[0175] According to the above method, a 2032 button half-cell test was prepared and tested under the condition of charge and discharge voltage range of 1.5~0.005V; according to the above method, a button cell full cell with a ternary positive electrode as the counter electrode was prepared and tested under the condition of charge and discharge voltage range of 3~4.2V. After testing, the first discharge capacity of the nano Si-Al@CG composite negative electrode material was 1900mAh / g, the first charge capacity was 1729mAh / g, the charge and discharge efficiency was 91%, and the lithium removal capacity at 0.2C rate was 1683mAh / g.
[0176] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A silicon-carbon composite material, characterized in that: It comprises porous carbon particles, graphene, nano-Si and nano-M; the porous carbon particles are coated with graphene; nano-Si and nano-M are deposited inside the porous carbon particles, between the porous carbon particles and the graphene, and on the surface of the graphene; The surfaces of the nano-Si and nano-M are coated with a carbon layer; The surfaces of the porous carbon particles and graphene are coated with a carbon layer; The M is selected from active metals.
2. The silicon-carbon composite material according to claim 1, characterized in that: The M is selected from one or more of Al, Ti and Ni; And / or, the mass ratio of the total mass of the nano-Si and the nano-M, the mass ratio of the porous carbon particles and the graphene is 40-55:55-60:1-10; And / or, the specific surface area of the silicon-carbon composite material is 1 to 4 m 2 / g; And / or, the pore size of the silicon-carbon composite material is 10 nm to 2 μm; And / or, the particle size D50 of the silicon-carbon composite material is 7-10 μm.
3. A method for preparing a silicon-carbon composite material, characterized in that: The following steps are involved: S1) Preparation of C@G precursor: The dispersant, the carbon source, the porous carbon particles and the graphene slurry are mixed and spray-dried to obtain a C@G precursor; S2) Preparation of Nano-Si-M@CG Intermediate: (1) heating the C@G precursor for preliminary carbonization; (2) continuously introducing silicon source gas, metal M compound gas and inert protective gas to perform the first insulation treatment; (3) stopping the introduction of silicon source gas and metal M compound gas, and continuously introducing carbon-containing gas and inert protective gas, and performing a second heat preservation treatment to obtain a nano-Si-M@CG intermediate; wherein M is selected from an active metal; S3) Preparation of silicon-carbon composite material: The nano-Si-M@CG intermediate is carbon coated to obtain a silicon-carbon composite material.
4. The preparation method according to claim 3, characterized in that: The heating rate in step (1) is 5 to 20°C / min; and / or, the temperature of the initial carbonization is 300° C. to 700° C.; and / or, the initial carbonization time is 1 to 2 hours; And / or, the preliminary carbonization is carried out under the condition of rotation; the rotation speed is 1-3r / min.
5. The preparation method according to claim 4, characterized in that: The preliminary carbonization in step (1) is carried out under vacuum conditions, and after the preliminary carbonization, silicon source gas is introduced for direct heat preservation treatment.
6. The preparation method according to claim 5, characterized in that: The vacuum degree of the vacuum condition is 1 to 100 Pa; And / or, the ratio of the amount of silicon source gas introduced to the porous carbon particles is (50-150) L: 1 kg; And / or, the temperature of the direct heat preservation treatment is 400° C. to 600° C.; And / or, the direct heat preservation treatment time is 0.5 to 2 hours.
7. The preparation method according to claim 3, characterized in that: In the step (2), the flow rates of the silicon source gas, the metal M compound gas and the inert protective gas are independently 0.1 to 4 L / min; And / or, the temperature of the first heat preservation treatment is 400° C. to 600° C.; And / or, the first heat preservation treatment time is 5 to 10 hours; And / or, the flow rates of the carbon-containing gas and the inert protective gas continuously introduced in step (3) are independently 1 to 5 L / min; And / or, the temperature of the second heat preservation treatment is 600° C. to 700° C.; And / or, the second heat preservation treatment time is 0.5 to 3 hours.
8. The preparation method according to claim 3, characterized in that: The dispersant is selected from one or more of carboxymethyl cellulose, polyvinyl pyrrolidone, polyethylene glycol and sodium dodecyl carbonate; The carbon source is selected from one or more of glucose, sucrose and polyacrylic acid; The silicon source gas is selected from one or more of monosilane, trisilane, dichlorosilane, trichlorosilane and tetrachlorosilane; The metal M-containing compound is selected from one or more of trimethylaluminum, aluminum hydride, nickel tetracarbonyl, 4-dimethylaminotitanium and titanium tetrachloride; The carbon-containing gas is selected from one or more of acetylene, ethylene and propane.
9. The preparation method according to claim 3, characterized in that: The carbon coating methods in step S3) are independently selected from pyrolysis and / or chemical vapor deposition.
10. A lithium ion battery, characterized in that: The invention comprises the silicon-carbon composite material according to claim 1 or 2 or the silicon-carbon composite material prepared by any one of the preparation methods of claims 3 to 9.
Citation Information
Patent Citations
High-energy-density and high-power-density negative electrode material for lithium ion battery and preparation method
CN109755522A
Nano silicon-carbon composite material for secondary lithium battery as well as preparation method and application of nano silicon-carbon composite material
CN115020689A
Silicon-carbon negative electrode material, preparation method and battery
CN116130637A